1988
DOI: 10.1177/106002808802200407
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine-Induced Acute Dystonic Reactions in the Presence of Metronidazole

Abstract: A 30-year-old woman underwent laparotomy and was placed on a seven-day course of metronidazole and ampicillin postoperatively. Chloroquine therapy for malaria was instituted on the sixth day and the patient developed acute dystonic reactions after a single dose. Diphenhydramine therapy before chloroquine administration did not prevent the development of the dystonic reactions. The extrapyramidal symptoms subsided upon diazepam administration and chloroquine withdrawal even though metronidazole therapy was cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…However, it has been linked to a reduction in forebrain catecholamine levels and an inhibition of neuronal calcium uptake. 19 This hypothesis could be supported in part by the effectiveness of benzodiazepines in the reversal of CQ-associated ADR. A normal balance between dopamine and acetylcholine in the basal ganglia involves modulation from gamma aminobutyric acid (GABA)-containing striatonigral neurons.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…However, it has been linked to a reduction in forebrain catecholamine levels and an inhibition of neuronal calcium uptake. 19 This hypothesis could be supported in part by the effectiveness of benzodiazepines in the reversal of CQ-associated ADR. A normal balance between dopamine and acetylcholine in the basal ganglia involves modulation from gamma aminobutyric acid (GABA)-containing striatonigral neurons.…”
Section: Discussionmentioning
confidence: 64%
“…18 Achumba et al reported a case of ADR after a single dose of CQ in a postoperative patient and in the presence of metronidazole. 19 The reported case suggested that the ADR might have been an idiosyncratic reaction and probably potentiated by the metronidazole. In our case, the ADR also occurred after a single dose of CQ but in the absence of any other medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 This assertion could be supported in part, by the observed effectiveness and symptom reversal of the dystonia by diazepam: it has been proposed that stimulation of the benzodiazepine receptors coupled to the γ-amino butyric acid (GABA) receptors via the chloride ion channel in the central nervous system facilitate GABA transmission, with a consequent inhibitory effect on muscle hypertonia and tremors. Other possible mechanisms that may underlie amodiaquine-associated adverse effects could be related to, CYP1A1 or 1B1-mediated extrahepatic metabolism of amodiaquine 3 , or biotransformation to chemically reactive electrophilic quinoneimine metabolites which, by forming immunogenic complexes, may lead to organ-specific toxicity in susceptible individuals.…”
Section: Discussionmentioning
confidence: 79%
“…The interaction between metronidazole and CQ associated with acute dystonic reactions such as facial grimacing, coarse tremors, and an inability to maintain posture in patient is reported [72].…”
Section: Metronidazolementioning
confidence: 99%